Designing a Firefighter Motorcycle as an Effort to Provide an Early Response to Fire Disaster / Himawan Hadi Sutrisno and Triyono - Hadi Sutrisno, Himawan; Triyono, Rizky Danu Rahmanto (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
As an effort to mitigate the fire disaster especially in densely populated areas with very narrow accesses, the author attempted to design a firefighter motorcycle by fulfilling the minimum equipment requirements for a firefighter motorcycle. In the process of the design, the type of the pump, the pump clutch, the pump bracket, and the dimensions of outlet and inlet pipes as well as the placement/storage of the hose and the fireproof suit in the motorcycle became the factors that were put into consideration. The motorcycle was also equipped with other firefighting equipment which would not ergonomically interfere with the motorcycle’s normal performance. This type of firefighter vehicle may be effective for such areas and suitable for an early response to the fire disaster due to its swift mobility to the fire location.